DEVELOPING A CHARACTER-BASED ENGLISH LANGUAGE TEXTBOOK FOR GRADE VIII OF JUNIOR HIGH SCHOOL BASED ON THE CURRICULUM 2013 - ., Ni Komang Ayu Sunaryati; ., Drs.Gede Batan,MA; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at developing a character-based English textbook for grade VIII of junior high school based on the curriculum 2013. It is categorized as a research and development study in which the product of the study was developed based on the modified instructional design of Dick, Carey, and Carey (2001), consisting of identifying the instructional goal, conducting instructional analysis, analyzing learners and context, writing performance objectives and indicators, developing judgment instrument, developing design of the textbook, developing content of the textbook, conducting formative evaluation, revising the textbook, limited field trial, and the final product. This research involved 32 students of class VIII.B6 of SMP N 6 Singaraja as the subjects and 2 experts as judges, i.e. a lecturer who is expert in materials development and an English teacher. The result of this study shows that the character values are accommodated in terms of content and presentation. The total mean score of the textbook’s content and presentation is 4.74 (Excellent) and the Cronbach’s Alpha coefficient reliability is 0.880 (Good). Besides, the result of the questionnaire after the limited field trial indicates that the students were interested and happy in using the developed textbook. In addition, based on the curriculum 2013, due to the implementation of scientific approach, the approach is presented in terms of the presentation of the textbook. Thus, the textbook developed in this research is very feasible to be used in teaching English for grade VIII of junior high school based on the curriculum 2013.keyword : English textbook, curriculum, curriculum 2013, character-based instruction